An Economy of Industries and its Aggregate Representation - Carlo D'Adda (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
The purpose of the present paper, in contrast, is to show that Keynes, in The general Theory, thought in more complex terme, referring to an economy made of industries in the Marshallian tradition.
Keywords: 330